Memorial Day Service Parade in Portugal Cove - Squires, Allen; Squires, Pearl (1962)
Photograph of Memorial Day Service Parade in Portugal Cove. Pearl Squires slide label identifies "Mr. Churchill World War I Veteran in Front" however man in centre has been identified by family members as Archibald Greeley.